Growth performance of bambara groundnut as influenced by phosphorus application using rock phosphate in the sub-humid tropical regions of Malaysia - Musa, M.; Massawe, F.; Mayes, S.; Alshareef, I.; Y., F. D. Dakora; Siddiqui, A. Singh (International Society for Horticultural Science, 2019)
Bambara groundnut (Vigna subterranea L. Verdc.) could be a potential crop for the future in Malaysia. However, its production in the sub-humid tropical regions such as Malaysia faces severe constraint due to inherent low soil phosphorus (P) content. Studies on the growth of the crop in response to P application using rock phosphate as a P source could provide information on how to address the constraint and increase the yield of the crop. A trial was carried out in the screen house of the University of Nottingham Malaysia Campus to study the growth of bambara groundnut as influenced by P application using rock phosphate in the region. The treatments consisted of factorial combination of two bambara groundnut landraces (‘Ex-Sokoto’ and ‘Kaaro’) and four levels of phosphorus (0, 20, 40 and 60 kg P2O5 ha-1 the equivalent of 0, 555.6, 1111.1 and 1666.7 kg ha-1 of Christmas Island Rock Phosphate (32% P2O5, 3.6% solubility using 2% neutral ammonium citrate)). The treatments were laid out in a completely randomized design (CRD) replicated three times. Results revealed that the ‘Kaaro’ landrace was higher than ‘Ex-Sokoto’ in most of the parameters measured at 4 weeks after sowing (WAS) but the two landraces were similar at 8 WAS in all the parameters measured except leaf area index which was higher in ‘Kaaro’. Application of P on the crop increased the leaf area index and plant dry weight at all sampling dates. It also increased the final root length, volume, weight and surface area. However, it decreased the initial root weight and root/shoot ratio at all sampling dates. Thus, both landraces could be selected for bambara groundnut production in the region. Rock phosphate could serve as alternative source of P for the production of bambara groundnut in the study area and was optimum at the application rate of 40 kg P2O5 ha-1 (1111.1 kg ha-1 of Christmas Island Rock Phosphate).